1964
DOI: 10.1029/rg002i001p00177
|View full text |Cite
|
Sign up to set email alerts
|

The variation of the deuterium content of natural waters in the hydrologic cycle

Abstract: Exploratory data from more than 1000 analyses of the distribution of deuterium in waters of the North American continent and the surface oceans contiguous to the continent are presented. The elementary theory of the processes that appear to explain the changes in the deuterium content of natural waters is developed. Quantitative expressions of the deuterium fractionation that can be expected to occur are presented for all phases of the hydrologic cycle from the evaporation of water from the oceans, its precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0

Year Published

1967
1967
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(112 citation statements)
references
References 18 publications
2
110
0
Order By: Relevance
“…Fractionation factors between vapor and liquid or vapor and solid (ice) decrease with increasing temperature (Akers, Welker, & Brook, 2017;Friedman, Redfield, Schoen, & Harris, 1964). Accordingly, higher air temperatures (positively correlated with cloud condensation temperature) lead to lower fractionation factors.…”
Section: Background Of Isotope Hydrologymentioning
confidence: 99%
“…Fractionation factors between vapor and liquid or vapor and solid (ice) decrease with increasing temperature (Akers, Welker, & Brook, 2017;Friedman, Redfield, Schoen, & Harris, 1964). Accordingly, higher air temperatures (positively correlated with cloud condensation temperature) lead to lower fractionation factors.…”
Section: Background Of Isotope Hydrologymentioning
confidence: 99%
“…In addition to simplifyin g th e operation (it is easie r to read a differe nce than to dial it out) 'fewer dial operated weights beco me involv ed so calibration un certainties are minimized. The requirements for large sensitivity and large on-s cale range taken together demand that the balance swing over a very large range in <P. But eq (10) shows that S is depende nt upon <P, except at the single point defined in eq (11), so that linearity is sacrificed to achieve sensitivity and range .…”
Section: The Balancementioning
confidence: 99%
“…These experiments were conducted prior to knowledge of isotopes, and we define "normal" water as that having a "normal" or "average" isotopic abundance ratio. Modern workers [11,12] have shown that th e isotopic abundance ratio in samples of water drawn from various locations on the earth may vary eno ugh to result in density differences of as much as 5 or more parts per million. Without knowledge of the isotopic abundance ratio in the water used in measuring the milliliter we are left with an un certainty of thi s amount in the accepted value of th e volume of the milliliter.…”
Section: Density Of Watermentioning
confidence: 99%
“…Water was extracted from hydrous minerals and fluid inclusions following the method of Friedman (1953). Isotopic ratios were determined for purified H 2 and CO2 gases on McKinney-Nier type mass spectrometers.…”
Section: Experimental and Theoret~al Backgroundmentioning
confidence: 99%